Characterization of Calcium Oxalate Hydrates and the Transformation Process. Issue 22 (23rd October 2020) - Valido, Iris H.; Rius‐Bartra, Joaquim M.; Boada, Roberto; Resina‐Gallego, Montserrat; Valiente, Manuel; López‐Mesas, Montserrat
Abstract: Calcium oxalate can be found in humans as kidney stones and in cultural heritage as films in two crystallographic species, dihydrate (COD/weddellite) and/or monohydrate (COM/whewellite). Due to its instability, COD is transformed into COM. Studying this crystalline conversion provides information about the origin of the monohydrated species, which will help in the assessment of prevention measurements to avoid their formation. In the present study, the synthesis of calcium oxalate hydrate microcrystals has been carefully performed to avoid mixture of phases in the final products; the long and short range order structure of both species have been studied by X‐ray diffraction (XRD) and X‐ray absorption spectroscopy (XAS), respectively. This structural information was considered in the density functional theory (DFT) computational study performed to assign the characteristic vibrational IR and Raman frequencies found. This detailed characterization allows an unambiguous assignment of the vibrations, thus providing the appropriate parameters required to monitor and characterize the transformation process. Abstract : Calcium oxalate hydrate microcrystals are carefully synthesized to avoid mixtures of phases in the final products. The long‐ and short‐range structures of the weddellite and whewellite species are studied by X‐ray diffraction and X‐ray absorption spectroscopy, respectively. This structural information is considered in a density functional theory study performed to assign the characteristic vibrational IR and Raman frequencies found. This detailed characterization allows an unambiguous assignment of the vibrations, thus providing the appropriate parameters required to monitor and characterize the transformation process.